Protection of Neonatal Broiler by Using T Cell Lymphokines Prepared from Immunization with Salmonella typhimurium Against Field Local Newcastle Disease Virus Isolate - Mohammed , Rashad A.; AL-Zuhariy, Mushtaq T.B. (International Journal of Poultry Science, 2018)
Objective: The current study aimed to use lymphokines from birds hyper-immunized against Salmonella typhimurum to enhance the immune response against Newcastle disease (ND) and to limit the use of vaccinal viruses that have been recently shown not to give absolute protection. Materials and Methods: Two groups of chicks were used: The first group was vaccinated with three doses of Salmonella typhimurum at 7, 14 and 21 days and the second group was not vaccinated and was considered a control group. Salmonella-immune lymphokines (S-ILK) were obtained from the T cells of the first group at 30 days, while non-immune lymphokines (N-ILK) were obtained from the T cells of the second group. Then, a total of 300 (Ross-308) 1 day old broiler chickens were randomly divided into 6 treatment groups (G1-G6) with 50 chicks in each group and treated as follows: G1: Treated with salmonella-immune lymphokines (S-ILK) and challenged with Newcastle disease virus (NDV). G2: Treated with non-immune lymphokines (N-ILK) and challenged with NDV. G3: Non-treated and challenged with NDV. G4: Non-treated and naturally infected with NDV. G5: Treated with salmonella-immune lymphokines S-ILK and not challenged. G6: Non-treated and non-challenged. Results: The results of immunity measured by ELISA and a hemagglutination inhibition test (HI) showed a significant decrease in the level (p<0.05) of maternal antibody titer (Abs) against ND on the seventh day after the challenge compared to the control group but on days 14 and 21, there was a slight increase in the level (p<0.05) of the antibody titer in G1 and G2 compared to the other groups in which no antibody titer was recorded. On the 28th day, the G3 and G4 groups recorded a significant increase (p<0.05) in the antibodies against ND and high mortality rates, while the G1 group revealed a moderate increase with no mortality. No titers were recorded in the G5 and G6 groups because they were not exposed to any challenge. Conclusion: The present study concludes that S-ILK provides absolute protection to chicks against NDV by enhancing their immune response and reduces virus isolation in living tissue following challenge with virulent local Newcastle isolate.